Analysis And Design of a Mobile-Based Point of Sale (POS) Application at Habibi Motor Workshop - Adam Madani Musalha; Ekatri Ayuningsih; Eko Afrianto (Cattleya Darmaya Fortuna, 2026)
The Development of information technology encourages MSMEs, including Workshop Habibi Motor, to improve operational efficiency and recording accuracy through digitalization. Manual transaction processes and stock management often cause problems such as data loss risk, delayed reports, and difficulties in performance analysis. This study designs a mobile-based Point of Sale (POS) application using the prototype method and FIFO algorithm to support more structured stock management. The application is developed with flutter as the front-enad, FastAPI as the back-end, and MySQL as the database. The results show that the application speeds up transactions, improves stock accuracy, and makes it easier for the workshop owner to monitor. The contribution of this research is supporting MSME digitalization through innovative mobile technology